Financial Management and Accounting Training for the Tourism Industry for Students at Taruna Bangsa Sawit Seberang Private High School - Deva Djohan; Ika Puspa Satriany; Robin; Thamrin; Duffin; Devia Febrina; Randy Brilliant Chandra; Emma Novirsari; Amin Hou; Iventura Fitra Uli Tamba (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service Program (PKM) aims to enhance the financial management and accounting skills of students at SMA Taruna Bangsa Sawit Seberang, specifically tailored for the tourism industry. The training focuses on key financial principles such as budgeting, financial reporting, cost management, and accounting practices within the tourism sector. By incorporating practical exercises, case studies, and simulations, students will gain hands-on experience in managing financial operations for tourism businesses. The program’s goal is to equip students with the necessary skills to manage finances effectively, thereby improving their job readiness in the growing tourism sector. The expected outcomes include increased financial literacy, better preparedness for careers in tourism, and a deeper understanding of how accounting plays a vital role in the industry’s success.